The use of Grice’s cooperative principle in Chinese TV talk shows / Yang Shuwei - Yang, Shuwei (2014)
This research uses the approach of discourse analysis (DA) to look at how a Chinese host in the TV talk show “Yang Lan One on One” interviews her guests who are native Mandarin speakers and native English speakers. The research focuses on two frameworks, one is Grice‟s Cooperative Principle (Grice, 1975) and the other is the repair strategies suggested by Cho and Larke (2010). The research attempts to examine if there are similarities and differences in the way the Chinese TV host observes Grice‟s four maxims i.e. the maxim of quality, the maxim of quantity, the maxim of relevance and the maxim of manner in her interviews of seven guests who come from three main backgrounds: actress, politician and athlete. These guests are also paired in terms of their native language i.e. one is from Mandarin background and one from English background as a way of ensuring some reliability. Cho and Larke (2010) framework is applied in the effort to understand how the interviewer (host) performs her repair strategies when the interviewees (guest) flout or violate Grice‟s Cooperative Principle. Three research questions are posed and the results are discussed. Data is downloaded from a public website and then manually transcribed verbatim. Non-English data are translated and precision is verified with the supervisor who is bilingual in the two languages. Six episodes of these interviews are compiled – three in Mandarin and three in English. Findings suggest that the Chinese host applies Grice‟s cooperative principles all the time in her interviews and she often uses confirmation as a way of understanding and to check her guest‟s message. However, she may adjust herself in the way she interviews the politicians. The findings of this research can enable foreign language learners of English in China to improve their communicative skills by observing Grice‟s Cooperative Principles adequately and precisely during conversations in order to avoid misunderstandings.